2010
DOI: 10.1002/cncr.25320
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and everolimus in the treatment of patients with metastatic melanoma

Abstract: BACKGROUND: In this phase 2 study, the activity and tolerability of the combination of bevacizumab, an inhibitor of angiogenesis, and everolimus, an inhibitor of the mammalian target of rapamycin (mTOR), was evaluated in the treatment of patients with metastatic melanoma. METHODS: Patients with metastatic melanoma who had received up to 2 previous systemic regimens (chemotherapy and/or immunotherapy) were eligible. Previous treatment with angiogenesis or mTOR inhibitors was not allowed. All patients received b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…The MTD for everolimus in this combination was 5mg daily, lower than the FDA approved monotherapy dose of 10mg daily. It is also lower than other bevacizumab-everolimus combinations, suggesting that the addition of chemotherapy results in overlapping toxicity (Altomare et al , 2011; Bullock et al , 2011; Hainsworth et al , 2010a; Hainsworth et al , 2010b). Treatment-related toxicity was consistent with the known toxicity profiles of each of these agents when used separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTD for everolimus in this combination was 5mg daily, lower than the FDA approved monotherapy dose of 10mg daily. It is also lower than other bevacizumab-everolimus combinations, suggesting that the addition of chemotherapy results in overlapping toxicity (Altomare et al , 2011; Bullock et al , 2011; Hainsworth et al , 2010a; Hainsworth et al , 2010b). Treatment-related toxicity was consistent with the known toxicity profiles of each of these agents when used separately.…”
Section: Discussionmentioning
confidence: 99%
“…It is also approved in combination with interferon α for the treatment of renal cell cancer (Escudier et al , 2007) and as a single agent for progressive glioblastoma (Vredenburgh et al , 2007). Multiple studies have reported that the combination of bevacizumab and everolimus is safe (Altomare et al , 2011; Bullock et al , 2011; Hainsworth et al , 2010a; Hainsworth et al , 2010b; Strickler et al , 2012; Vlahovic et al , 2012). Clinically significant toxicities include: fatigue, mucositis, hypertension, vomiting, diarrhea, proteinuria, fistula/abscess/perforation, and hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The PFS or OS probability within the specified interval was infrequently reported when results were presented and median survival was reported instead. One interesting example of dichotomizing PFS was the trial in Hainsworth et al (2010) where the PFS rate at 6 weeks was used for futility stopping in Simon’s design, and the PFS rate at 12 weeks was used for the final analysis.…”
Section: Primary Endpoint and Statistical Designmentioning
confidence: 99%
“…The patients were not molecularly profiled before enrollment. A Phase II study that incorporated an angiogenesis inhibitor bevacizumab with the mTOR inhibitor everolimus reported that 12% of melanoma patients achieved a major response [40]. Currently, a Phase II trial of the mTOR inhibitor temsirolimus combined with the MEK inhibitor AZD 6244 in treatment-naive patients with BRAF -mutant stage IV melanoma is ongoing.…”
Section: Mtormentioning
confidence: 99%